2022
DOI: 10.1152/ajpheart.00072.2022
|View full text |Cite
|
Sign up to set email alerts
|

Matrix anisotropy promotes angiogenesis in a density-dependent manner

Abstract: Angiogenesis is necessary for wound healing, tumorigenesis, implant inosculation, and homeostasis. In each situation, matrix structure and mechanics play a role in determining whether new vasculatures are able to establish transport to new or hypoxic tissues. Neovessel growth and directional guidance are sensitive to 3D matrix anisotropy and density, although the individual and integrated roles of these matrix features have not been fully recapitulated in vitro. We developed a tension-based method to align 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…To highlight the crucial role that the degree of anisotropy plays during cell guidance, we simulated microvessel growth using either vector fields or EFD fields. Simulations were generated to correspond to experiments from our recent in vitro study on the roles of matrix density and anisotropy during angiogenesis [ 1 ]. Microvessel culture was performed or simulated in low, medium, or high degrees of collagen alignment as well as low or high collagen density (Figs 2 , 3A , and S3A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To highlight the crucial role that the degree of anisotropy plays during cell guidance, we simulated microvessel growth using either vector fields or EFD fields. Simulations were generated to correspond to experiments from our recent in vitro study on the roles of matrix density and anisotropy during angiogenesis [ 1 ]. Microvessel culture was performed or simulated in low, medium, or high degrees of collagen alignment as well as low or high collagen density (Figs 2 , 3A , and S3A ).…”
Section: Resultsmentioning
confidence: 99%
“…This anisotropy contributes to durotaxis via guidance of cells along variously-tensed fibrils, as well as contact guidance and haptotaxis–the guidance of cells by matrix binding site gradients (e.g., integrins) [ 11 , 12 ]. In a recent study, we demonstrated that both microvessel rate of extension and guidance (reorientation and taxis) increased with matrix anisotropy during in vitro microvascular angiogenesis [ 1 ]. Interestingly, collagen density attenuated the effects of anisotropy so that stronger alignment was required for significant proangiogenic effects to occur in dense scaffolds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary challenges in CTE are 1) vasculogenesis -for efficient exchange of oxygen between the cells and blood- and 2) mimicking the complex structure of the myocardium ( Vunjak-Novakovic et al, 2011 ; Izadifar et al, 2014 ; Kitsara et al, 2017 ). The orientation of the extracellular matrix fibrils can change vascularization by affecting the migration and polarization of endothelial cells, their branching, formation of basement membrane, and cellular traction ( Labelle et al, 2022 ). Thus, to replicate the complex structure of the human heart tissue, many parameters including alignment of the cells within the fibrils should be appropriately designed and controlled ( Zhang et al, 2015 ; Qasim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%